Syed M. Naquib Al-Attas’ Thoughts on the Islamization of the Tax Concept - Sarina Junita; Niken Baramurti Evieta Enggar Sandy; Helmi Syaifuddin (al-Afkar, Journal For Islamic Studies, 2026)
As the primary source of state revenue for funding various public needs, taxes are a financial obligation and a form of community contribution in encouraging social and economic development. A practical and fair tax revenue system can be an essential foundation for sustainable economic growth and the creation of social stability. This research discusses the concept of tax Islamization according to Syed M. Naquib Al-Attas. Al-Attas argues that tax Islamization aims to reform the tax system to follow Sharia principles, emphasizing justice, social responsibility, and economic sustainability. In the framework of Islamization, taxes are not only seen as a fiscal instrument but also as a spiritual and social means to achieve people's welfare. Al-Attas proposed the integration of zakat as the primary mechanism in replacing the conventional tax system, highlighting the importance of Islamic ethical values, such as monotheism, amanah, and Ihsan, in tax management. This study uses a qualitative method with a literature study approach. The results of this study show that the concept of tax, according to al-Attas, must be integrated with Islamic principles because there are secular elements in the existing tax concept and taxes can be a tool to achieve justice and the welfare of the people.